Non-electrocardiography- and electrocardiography-gated computed tomography angiography for the evaluation of feline coronary arteries - Kim, Junyoung; Kim, Dae-Hyun; Kim, Kitae; Oh, Dayoung; Yoon, Junghee (Frontiers in Veterinary Science, 2022)
Objectives: Few studies have directly compared the clinical feasibility of electrocardiography-gated and non-electrocardiography-gated multidetector computed tomography for evaluating coronary arteries in veterinary medicine. We aimed to characterize and visualize feline coronary arteries using these two imaging modalities. Methods: This prospective, controlled, comparative pilot study examined six client-owned cats (five clinically normal, one with hypertrophic cardiomyopathy) using non-electrocardiography-gated and retrospective electrocardiography-gated scans. Optimal non-electrocardiography scan timing or electrocardiography-gated R-R reconstruction interval for coronary artery visualization was determined. The degree of opacification and sharpness of proximal coronary branches were subjectively graded; coronary dominance, left coronary artery branching types, and diameter and length of coronary artery branches were also assessed. Results: Non-electrocardiography-gated images provided the least information on the bilateral coronary artery ostium and proximal segments, while electrocardiography-gated images clarified the detailed course of the main coronary branches at diastole in all cats. The degree of opacification and sharpness of coronary artery were subjectively evaluated as good/excellent in all cats. Coronary dominance (left: four; right: two) and left coronary artery branching types (three different patterns, two additional tortuous branches) varied. Body weight and sex were not significantly associated with coronary artery length or diameter. Vertebral heart scale scores positively correlated with the right coronary artery and negatively correlated with the left main coronary artery. Clinical significance: Electrocardiography-gated multidetector computed tomography provides images with adequate resolution to identify the anatomy of feline coronary arteries. Detailed morphological knowledge of feline coronary vessels will enable novel diagnostic and therapeutic methods in veterinary medicine.